2019
DOI: 10.1111/bju.14639
|View full text |Cite
|
Sign up to set email alerts
|

In utero myelomeningocoele repair and urological outcomes: the first 100 cases of a prospective analysis. Is there an improvement in bladder function?

Abstract: Objectives To evaluate the first 100 cases of in utero myelomeningocoele (MMC) repair and urological outcomes in a prospective analysis aiming to define possible improvement in bladder function. Patients and methods We used a protocol consisting of a detailed medical history, urinary tract ultrasonography, voiding cystourethrography, and urodynamic evaluation. Patients were categorised into four groups: normal, high risk (overactive bladder with a detrusor leak‐point pressure >40 cm H2O and high filling pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…While the MOMS trial demonstrated [3] (and our center delivered confirmative data [1]) that fetal OSB repair indeed is able to preserve neurologic lower extremity function and dramatically decreases rates of shunt-dependent hydrocephalus, the effect on the urological outcome remains unclear. Several studies on the urological outcome after in utero OSB repair were published [4][5][6][7][8][9][10][11][12][13][14][15][16][17], however reporting controversial results. The aim of this study was to further increment urological outcome data by analyzing our own cohort of patients who underwent in utero OSB repair, and to demonstrate that our earlier published positive preliminary results [7] are permanent.…”
Section: Introductionmentioning
confidence: 99%
“…While the MOMS trial demonstrated [3] (and our center delivered confirmative data [1]) that fetal OSB repair indeed is able to preserve neurologic lower extremity function and dramatically decreases rates of shunt-dependent hydrocephalus, the effect on the urological outcome remains unclear. Several studies on the urological outcome after in utero OSB repair were published [4][5][6][7][8][9][10][11][12][13][14][15][16][17], however reporting controversial results. The aim of this study was to further increment urological outcome data by analyzing our own cohort of patients who underwent in utero OSB repair, and to demonstrate that our earlier published positive preliminary results [7] are permanent.…”
Section: Introductionmentioning
confidence: 99%
“…Since first MMC closure 1998 (44), nine reports of urological outcomes on 291 cases have been published worldwide (4552). Most reports that compared early bladder function of MMC patients treated pre- or post-natally failed to show nay advantages.…”
Section: Resultsmentioning
confidence: 99%
“…The initial evaluation, with an average age of 5.8 months, showed high risk in 52.6%, incontinent in 27.4%, with underactive bladder in 4.2% and only 14.7% had a normal bladder profile. CIC was initiated in 57.3% of the patients and anticholinergics in 52.6% 10 . In another comparative study involving patients from the same database, we evaluated 88 patients in group 1 (prenatal surgery), 86 in group 2 (postnatal surgery), and a third group, subgroup 2, with 38 patients who started urological evaluation at <12 months of age.…”
Section: Discussionmentioning
confidence: 99%